The grim grotto - Snicket, Lemony (Snicket, Lemony. Series of unfortunate events, 2018)
Still pursued by the evil Count Olaf, the Baudelaire orphans attempt to reach a very important VFD meeting, but first they must travel in a rattletrap submarine to the Gorgonian Grotto, a dangerous underwater cave, in search of the sugar bowl.